The Mediterranean diet : an evidence-based approach - Preedy, Victor R.; Watson, Ronald R. (Ronald Ross) (Academic Press, 2020)
The Mediterranean Diet: An Evidence-Based Approach, Second Edition provides authoritative material on the many facets surrounding the complex interrelationships between diet, nutrition, health and well-being. The book discusses historical, cultural and scientific foundations, with chapters delving into nutritional adequacy, agricultural practices, food culture, mortality, quality of life, children and adolescents, behavior, cardiovascular diseases, diet quality, nutritional knowledge, nuts, minerals, olive oil, hydroxytyrosol, water, antioxidant nutritional status, ketogenics, adiposity, metabolic syndrome, type 2 diabetes, cardiovascular risk, nutrigenetics, epigenetics, the link between epigenetics and pregnancy, gene polymorphisms bone health, insulin signaling inflammatory gene expression, and more. --